Combined Effect of Compaction Methods and Loading Conditions on the Deformation Behaviour of Unbound Granular Material. (22nd July 2020) - Ren, Jiaolong; Li, Di; Wang, Siyuan
Abstract : Unbound granular material is an important construction material that is used for flexible pavement. As one of the most important indices used for describing the properties of unbound granular material, the deformation characteristic is significantly influenced by the compaction method used. However, the effects of the compaction method on the deformation behaviour are neglected in the existing studies. Hence, we investigate the deformation characteristics of unbound granular material produced by the vertical vibration compaction method (VVCM) and the modified Proctor compaction method (MPCM) via repeated triaxial load tests and reveal the effect of loading conditions and aggregate gradations. The results show that (a) the deformation of unbound granular material decreases as the stress level and confining pressure are increased; (b) the deformation resistance of unbound granular material produced by the VVCM is superior to that produced by the MPCM; (c) the difference of deformation resistance arising between using the VVCM and MPCM decreases as confining pressure increases and is not significant with changes in the stress level; (d) the extent of various factors on deformation characteristics from greatest to least is as follows: stress level > aggregate gradation > compaction method > confining pressure; and (e) increasing the content of coarse aggregates is conducive to enhancing the deformation resistance of unbound granular material, particularly for the VVCM. Finally, a simple approach for modelling and predicting deformation is established.